The Reality of Using Finger Spelling to Develop Reading Skills for Deaf Students from their Primary School Teachers Point of View in Al-Amal Institutes and Inclusion Schools in Jeddah City - Alzahrani, Norah Saleh Ahmed; Alghamdi, Mazen Abdulrahman (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the reality of using finger spelling to develop reading skills for deaf students from the point of view of primary school teachers for deaf students in Al-Amal institutes and inclusion schools in Jeddah city. To achieve the objectives of this study, a questionnaire was developed consisting of (33) items distributed on (5) dimensions related to reading skills, which are: (phonological awareness, coding of sounds, vocabulary, reading fluency, reading comprehension), and 35 female teachers for deaf students in the primary stage answered them. The results resulted in a medium approval degree of their usage of finger spelling to develop reading skills among Deaf female students in the primary stage in general from their point of view, where it came in the first place after encoding sounds with a degree of agreement, then the remaining four dimensions with a degree of medium agreement arranged in descending order as follows: (reading fluency, vocabulary, reading comprehension, phonemic awareness), and the results indicated that, there are no statistically significant differences in the responses of the study sample due to the following variables: educational qualification, years of experience, academic grade, and subject.